Computational Docking Studies of Phenyl Acetic Acid Derivatives with Biological Targets, DNA, Protein and Enzyme - Ali, Zafar (Journal of Chemistry and Environment, 2024)
Phenyl acetic acid (PAA) is a well-known biomolecule used in antibiotics and drugs. To elucidate the binding modes of PAA and its derivatives with DNA, Pim kinase protein, and urease enzymes, molecular docking studies were conducted. The results revealed that PAA and its derivatives intercalate with DNA, disrupting its structure and potentially affecting replication, transcription, and repair processes. The 3-chloro-PAA showed the highest docking score (-7.809) and significant polar interactions with DNA residues. For Pim kinase, the compounds exhibited polar interactions with key residues, with 2-propyl PAA demonstrating notable inhibitory effects. Similarly, PAA derivatives interacted effectively with urease enzymes, with the 4-propyl-PAA showing a strong docking score (-8.5250). Overall, the meta-substituted PAAs exhibited superior binding interactions compared to ortho and para-substituted derivatives, suggesting their potential as effective inhibitors for these biological targets.